2019
DOI: 10.1164/rccm.201904-0717st
|View full text |Cite
|
Sign up to set email alerts
|

The Occupational Burden of Nonmalignant Respiratory Diseases. An Official American Thoracic Society and European Respiratory Society Statement

Abstract: Workplace inhalational hazards remain common worldwide, even though they are ameliorable. Previous American Thoracic Society documents have assessed the contribution of workplace exposures to asthma and chronic obstructive pulmonary disease on a population level, but not to other chronic respiratory diseases. The goal of this document is to report an in-depth literature review and data synthesis of the occupational contribution to the burden of the major nonmalignant respiratory diseases, including airway dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
204
4
19

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 306 publications
(272 citation statements)
references
References 222 publications
7
204
4
19
Order By: Relevance
“…Chronic obstructive pulmonary disease (COPD) is a progressing condition with accelerated lung function decline, which requires early recognition and treatment and is often associated with smoking, 1,2 air pollution, 3,4 and occupational exposure to noxious gases and particles in the workplace. 5 A recent comprehensive review on the occupational burden of respiratory disease concluded that every tenth COPD case may be attributed to hazardous occupations. 5 Occupational surveillance programs are therefore essential to detect accelerated lung function decline in those at risk, to offer smoking cessation and increase workers' awareness of the inhaled hazards.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic obstructive pulmonary disease (COPD) is a progressing condition with accelerated lung function decline, which requires early recognition and treatment and is often associated with smoking, 1,2 air pollution, 3,4 and occupational exposure to noxious gases and particles in the workplace. 5 A recent comprehensive review on the occupational burden of respiratory disease concluded that every tenth COPD case may be attributed to hazardous occupations. 5 Occupational surveillance programs are therefore essential to detect accelerated lung function decline in those at risk, to offer smoking cessation and increase workers' awareness of the inhaled hazards.…”
Section: Introductionmentioning
confidence: 99%
“…5 A recent comprehensive review on the occupational burden of respiratory disease concluded that every tenth COPD case may be attributed to hazardous occupations. 5 Occupational surveillance programs are therefore essential to detect accelerated lung function decline in those at risk, to offer smoking cessation and increase workers' awareness of the inhaled hazards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OA is defined as asthma that is caused by workplace exposures, while WEA is defined as a worsening of existing asthma due to the workplace environment. On the basis of the statements from the American Thoracic Society, 16% of incident asthma among adults is attributable to the workplace, while WEA has a 21.5% prevalence among adults with asthma 4,5 . WRA can be costly.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the statements from the American Thoracic Society, 16% of incident asthma among adults is attributable to the workplace, while WEA has a 21.5% prevalence among adults with asthma. 4,5 WRA can be costly. Follow-up studies of OA cases reported prolonged unemployment rates of 14% to 69% and rates of lost income ranging from 44% to 72%, with similar results for WEA cases.…”
Section: Introductionmentioning
confidence: 99%